2011
DOI: 10.1007/s11060-010-0513-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of heme oxygenase-1 enhances anti-cancer effects of arsenic trioxide on glioma cells

Abstract: We have previously reported that arsenic trioxide (ATO) could inhibit glioma growth both in vitro and in vivo, and demonstrated its potent therapeutic effects on gliomas. In this study we showed that ATO induced cell damage and heme oxygenase-1 (HO-1) expression in glioma cells via ROS generation. HO-1 inducer clearly protected from ATO-induced cell death and ROS generation, and HO-1 inhibitor led to a significant increase in cell death and ROS generation induced by ATO. In addition, knockdown of nuclear facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Hormetic effect of arsenic-induced HO-1 expression HO-1 has been shown to protect cells in different stress models, but the results of studies regarding the cytoprotective effect of HO-1 up-regulation in response to arsenic have been inconclusive (Liu et al 2011b;Morales et al 2009). As a result, we used zinc protoporphyrin IX (ZnPP), a well-documented HO-1 competitive inhibitor, to examine the effect of HO-1 on arsenic-induced cytotoxicity.…”
Section: Cytotoxicity Of Arsenic Can Be Reduced By A-lipoic Acid and mentioning
confidence: 99%
“…Hormetic effect of arsenic-induced HO-1 expression HO-1 has been shown to protect cells in different stress models, but the results of studies regarding the cytoprotective effect of HO-1 up-regulation in response to arsenic have been inconclusive (Liu et al 2011b;Morales et al 2009). As a result, we used zinc protoporphyrin IX (ZnPP), a well-documented HO-1 competitive inhibitor, to examine the effect of HO-1 on arsenic-induced cytotoxicity.…”
Section: Cytotoxicity Of Arsenic Can Be Reduced By A-lipoic Acid and mentioning
confidence: 99%
“…A number of studies have shown that an increase in ROS-scavenging and -detoxifying enzymes protects cells, whereas blocking these defense systems confers sensitivity to ionizing radiation (IR) or chemotherapeutic drugs [6][7][8]. Most of these antioxidant proteins are regulated through the interaction of the transcription factor Nrf2 (NF-E2-related factor 2) with a cis-element in an antioxidant-response element (ARE) sequence located in the promoter of the corresponding gene.…”
Section: Introductionmentioning
confidence: 99%
“…We found that knockdown of HO-1 by means of small interfering RNA (siRNA) resulted in the induction of apoptosis in SW480 human colon cancer cells in culture [Fang et al, 2003]. Liu et al [2011] reported that Nrf2 knockdown effectively led to suppressed HO-1 expression and enhanced sensitization to arsenic trioxide-induced apoptosis in cultured human glioma cells U251MG and A172. Quite recently, HO-1 expression was found to be regulated post-transcriptionally by microRNA (miRNA).…”
Section: Ho-1 As a Target For Chemosensitization: The Therapeutic Potmentioning
confidence: 99%
“…Antitumor and chemosensitizing effects of metalloporphyrin-type HO inhibitors such as zinc protoporphyrin (ZnPP) and cobalt protoporphyrin have been demonstrated in cultured tumor cells and in animal models [Doi et al, 1999;Fang et al, 2003Fang et al, , 2004bLiu et al, 2011;Tanaka et al, 2003]. Combining chemotherapeutic agents such as camptothecin, doxorubicin, arsenic trioxide, gemcitabine, and imatinib, as well as irradiation, with ZnPP or related inhibitors may lead to improved antitumor treatment [Fang et al, 2004b;Gleixner et al, 2009;Liu et al, 2011;Mayerhofer et al, 2008;Miyake et al, 2010].…”
Section: Antioxidant Adaptive Response Of Malignant Glioma Related Tomentioning
confidence: 99%
See 1 more Smart Citation